Numerical Investigation of Forced Convection Heat Transfer on a Circular Finned tube with AL2O3-Water Nano Fluid (International Journal of Scientific Research and Management (IJSRM), 2018)
This paper presents a three-dimensional numerical analysis to study the laminar forced convection heat transfer and flow characteristics of AL2O3–water Nano fluid with Solid particles less than 100 nm through a tube with 1m Length and 25 mm inner diameter and 30mm outer diameter contains circular fins with 30mm inner diameter and 50mm outer diameter with thickness of 2mm , investigated numerically by using finite volume method, models using ANSYS 14.5 Based on the single-phase approach, The flow of fluid is assumed to be incompressible, steady and laminar with various thermo physical properties according to volume concentration of Nano particles The Navies Stokes equations along with the energy equation have been solved by using SIMPLE algorithm Technique. The effects of different parameters such as nanoparticle volume concentration (1%, 3% and 5%), and Reynolds number are varied from (500 - 2100) for various axial locations of tube with AL2O3–water fluids and the effect of different values of velocity at the tube inlet will be studied during this paper. Where the results showed that the coefficient of heat transfer increases when the concentration of Nano fluid increase.